Research on the Teaching Reconstruction and Practice of Knowledge Graph-Empowered Smart Classrooms—A Case Study of the Linear Algebra Course - Shi, Qinxian (Journal of Research in Vocational Education, 2026)
In response to problems in traditional linear algebra classroom teaching, including linearized knowledge presentation, implicit logical relationships, and delayed feedback on learning conditions, this paper proposes and practices a teaching model empowered by knowledge graphs. Relying on a smart teaching platform, the knowledge graph is transformed from a static teaching resource into a dynamic knowledge navigation system. This paper focuses on the application mechanisms of knowledge graphs across the full teaching chain, including pre-class guided learning, in-class generative teaching, and post-class precise evaluation, and constructs a classroom paradigm of visualized navigation—structured interaction—personalized extension. Teaching practice shows that this model can effectively reduce the cognitive load of abstract concepts, significantly improve students’ level of knowledge structuring and classroom participation, and provide a practical path of reference for the substantive implementation of smart courses.